A Critical Examination of Nepal's National AI Policy 2081(2025): SWOT Analysis and Strategic Recommendations for Sustainable AI Integration - Mahat, Dipak; Neupane, Dasarath; Shrestha, Sajeeb Kumar (Nepal Journal of Multidisciplinary Research, 2025)
Background: Nepal’s National AI Policy 2081 is positioned as a cornerstone for AI-driven national growth, with a focus on agriculture, healthcare, and education. However, challenges such as limited infrastructure, a shortage of skilled professionals, and low AI awareness persist. This study critically evaluates the policy through a SWOT analysis. Methods: A qualitative research approach was employed, utilizing thematic content analysis to review Nepal’s AI policy alongside global AI frameworks. Secondary data from policy documents, academic literature, and reports were analyzed to identify the policy's strengths, weaknesses, opportunities, and threats, and to propose strategies for improving its efficacy. Results: The SWOT analysis revealed key strengths, including a clear vision for AI-driven digital transformation, a sector-focused AI approach, promotion of AI research and ethical governance, and investment in AI entrepreneurship. Weaknesses identified include a lack of an implementation roadmap, limited AI infrastructure, outdated data governance laws, and insufficient strategies for mitigating job displacement. Opportunities highlighted include AI as a driver for economic growth, public service efficiency, and agricultural innovation. However, threats such as inadequate AI infrastructure, cybersecurity risks, and AI bias were also noted. Conclusion: Nepal’s AI Policy 2081 marks significant progress in recognizing AI’s potential. However, its success will depend on addressing its infrastructural, regulatory, and socio-economic gaps. A more defined implementation roadmap, investment in infrastructure, and strategies for addressing potential job displacement are crucial for sustainable development. Novelty: It provides context-specific strategies to integrate AI equitably within the socio-economic landscape of developing nations.